Everyday probability and statistics health, elections, gambling and war - Woolfson, Michael M. (London : Imperial College Press ; Singapore ; Hackensack, NJ Distributed by World Scientific Pub., 2012)
Probability and statistics impinge on the life of the average person in a variety of ways--as is suggested by the title of this book. Very often, information is provided that is factually accurate but intended to present a biased view. This book presents the important results of probability and statistics without making heavy mathematical demands on the reader. It should enable an intelligent reader to properly assess statistical information and to understand that the same information can be presented in different ways. In this second edition, the author presents a new chapter exploring science and society including the way that scientists communicate with the public on current topics such as global warming. The book also investigates pensions and pension policy, and how they are influenced by changing actuarial tables
The nature of probability -- Combining probabilities -- A day at the races -- Making choices and selections -- Non-intuitive examples of probability -- Probability and health -- Combining probabilities : the craps game revealed -- The UK National Lottery, loaded dice and crooked wheels -- Block diagrams -- The normal (or Gaussian) distribution -- Statistics : the collection and analysis of numerical data -- The Poisson distribution and death by horse kicks -- Predicting voting patterns -- Taking samples : how many fish in the pond? -- Differences : rats and IQs -- Crime is increasing and decreasing -- My Uncle Joe smoked 60 a day -- Chance, luck and making decisions -- Science and society -- The pensions problem -- Solutions to problems.
Includes bibliographical references and index.
Keywords: Probabilities; Statistics; Probabilities -- Problems, exercises, etc; Statistics -- Problems, exercises, etc